2006
DOI: 10.3892/ijmm.17.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacteriophage in the treatment of experimental animal bacteremia from imipenem-resistant Pseudomonas aeruginosa

Abstract: Abstract. The emergence of antibiotic-resistant bacterial strains still remains a significant problem for antimicrobial chemotherapy in the clinic. Bacterial viruses (bacteriophages or phages) have been suggested to be used as alternative therapeutic agents for bacterial infections. However, the efficacy of phage therapy in treating drug-resistant infections in humans is uncertain. Therefore in the present study, we examined the effectiveness of phages in the treatment of imipenem-resistant Pseudomonas aerugin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 12 publications
3
69
0
2
Order By: Relevance
“…Phages have recently been used to treat murine peritonitis and bacteremia (7,32,33). Watanabe et al (33) had limited success using lytic bacteriophages to treat peritonitis, whereas Hagens et al (7) showed better efficacy using a lysis-deficient, nonreplicating phage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phages have recently been used to treat murine peritonitis and bacteremia (7,32,33). Watanabe et al (33) had limited success using lytic bacteriophages to treat peritonitis, whereas Hagens et al (7) showed better efficacy using a lysis-deficient, nonreplicating phage.…”
Section: Discussionmentioning
confidence: 99%
“…The latter might be predicted based on the ability of bacteriophages to enter the circulating blood rapidly after i.p. administration (5,20,32).…”
Section: Discussionmentioning
confidence: 99%
“…The phage was shown to overcome a high-dose, systemic bacterial infection as well as wound infection in mice. Thus, the study demonstrated that the therapeutic efficacy of the phages was independent of the administration routes, but overall, the timing of administration is very important [57]. Another study focused on the details of multiplicity of infection (MOI) of phage against multidrug-resistant uropathogenic E. coli (UPEC).…”
Section: Phages Therapy In Animal Models Of Human Infectionmentioning
confidence: 99%
“…[49], vancomycin-resistant Enterococci [50][51][52], antibiotic-resistant Staphylococci [53,54], multidrugresistant Klebsiella pneumonia [55], imipenem-resistant [56,57] and multidrug-resistant Pseudomonas aeruginosa [58,59], antibiotic-resistant strains of Escherichia coli [60], and methicillin-resistant Staphylococcus aureus [61]. Today, there are several different antibacterial strategies derived from phages including enzybiotics (cloned host-specific, phageencoded lytic enzymes introduced to combat bacteria without the whole phage) and whole-phage therapy (introducing whole, viable phage to attack the infecting bacteria) [8,[62][63][64].…”
Section: Medical and Therapeutic Application Of Bacteriophagesmentioning
confidence: 99%
“…Treatment with bacteriophage is associated with numerous advantages over chemotherapy: (i) it is economic and effective against multidrug-resistant bacteria because the mechanisms by which it induces bacteriolysis differ completely from those of antibiotics, (ii) it is safe because it has high specificity for its target and neither disturbs the microflora of the body nor affects eukaryotic cells, and (iii) administration requires only a single dose of treatment, owing to its selfreplicating nature (1,37). Although bacteriophage therapy has been successfully used to treat various diseases in both animals (4,8,10,11,25,32,40,41,44) and humans (1,5,17,37,42), there is no report associated with phage therapy of K. pneumoniae-induced liver abscesses. In the present study, the therapeutic effect of a newly isolated phage (NK5) with lytic activity for K. pneumoniae was evaluated against K. pneumoniae infection.…”
mentioning
confidence: 99%